FAKTOR - FAKTOR YANG MEMPENGARUHI KEPATUHAN PENGGUNAAN ALAT PELINDUNG DIRI (APD) PADA PERUSAHAAN DAERAH AIR MINUM (PDAM) KOTA BALIKPAPAN - Maslina, Maslina; Fuadi, Yan; Arrijal, Achmad Nafi (IDENTIFIKASI, 2021)
Obedience is like obeying orders, obeying orders or rules. Meanwhile, compliance is behavior according to the rules and discipline. The work of operators in the production department is a job that requires expertise, creativity and high concentration in doing work because the workplace is exposed to a lot of dust and chemicals, besides that personal protective equipment (PPE) is an important component in reducing exposure to dust and chemicals. to operator workers. The purpose of this study was to analyze the factors related to operator worker compliance in the use of Personal Protective Equipment (PPE). This study uses the observation method and the interview method with a Cross Sectional approach which is carried out with the Chi-Square test. The subject of this research is the total sampling that is in the production section as many as 25 respondents. Based on the Chi-Square statistical test, it was found that attitudes and supervision had p-value <0.05, while the level of knowledge and condition of PPE had p=value> 0.05. The conclusion of this study is that there is a relationship between attitudes and supervision in the use of PPE with worker compliance in the use of PPE, while the variable level of knowledge and condition of PPE did not find a significant relationship with worker compliance in the use of PPE. Key Words: PPE, Compliance, PPE Condition Knowledge, Supervision, Attitude